2014
DOI: 10.1186/1471-2458-14-938
|View full text |Cite
|
Sign up to set email alerts
|

Structural and intermediary determinants of social inequalities in the mental well-being of European workers: a relational approach

Abstract: BackgroundThe objective of this study is to examine social inequalities in employee mental well-being, using relational social class indicators. Relational social class indicators are based on theoretical insights about the mechanisms generating social (health) inequalities. Additionally, it is examined whether the psychosocial work environment and employment quality act as intermediary determinants of social class inequalities in mental well-being, simultaneously testing the mediation (differential exposure) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 40 publications
2
23
0
1
Order By: Relevance
“…The worst health status of nonskilled workers has been reported in other studies from Western countries [14, 15, 4345]. This study adds an additional support for these prior findings in a relatively newly developed Asian capitalist country.…”
Section: Discussionsupporting
confidence: 86%
“…The worst health status of nonskilled workers has been reported in other studies from Western countries [14, 15, 4345]. This study adds an additional support for these prior findings in a relatively newly developed Asian capitalist country.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, educational level had negligible impacts on subsequent sickness absence due to mental disorders. However, more detailed sensitivity analyses (data not shown) showed that educational groups had very similar amounts of subsequent long sickness absence, except the group with the highest education had less than others, which is in line with a previous study [21]. …”
Section: Discussionsupporting
confidence: 89%
“…In addition, although we focus here on the unemployed versus the employed, we recognize that within these two groups there are also important differences. For the unemployed these include, for example the duration and the reason of job loss [ 100 ], and for the employed, intrinsic and extrinsic job characteristics [ 40 , 41 ]. These differences might also be related to mental health and mental health care use.…”
Section: Discussionmentioning
confidence: 99%